(untitled) (Oshada, 2025)
Chronic diseases, such as diabetes mellitus, hypertension, heart failure and COPD, are the leading causes of morbidity and mortality in Indonesia, putting a strain on the health system and patients’ quality of life. Continuous monitoring and effective management are essential, but are often constrained by limited access to healthcare services. Mobile-based health technology, or Mobile Health (mHealth), offers an innovative solution to improve monitoring of patients with chronic diseases, allowing patients to self-monitor their conditions and interact with medical personnel virtually. Despite its great potential, the implementation of mHealth faces challenges such as limited digital infrastructure, access gaps, as well as low digital literacy of patients, especially the elderly and those with low education. To address these challenges, a SWOT analysis was used to identify the strengths, weaknesses, opportunities and threats faced by this technology. The strengths of mHealth lie in real-time monitoring efficiency and accessibility, while the weaknesses lie in infrastructure dependency and potential inequality of access. Opportunities for mHealth development are promising, but face threats such as weak regulations and data misuse. The implementation of mHealth requires comprehensive policies, strict regulations, and continuous education to be effective in improving the quality of chronic disease monitoring in Indonesia